2002
DOI: 10.1097/00001622-200201000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heterozygosity as a predictor to map tumor suppressor genes in cancer: molecular basis of its occurrence

Abstract: High frequency of chromosomal deletions elicited as losses of heterozygosity is a hallmark of genomic instability in cancer. Functional losses of tumor suppressor genes caused by loss of heterozygosity at defined regions during clonal selection for growth advantage define the minimally lost regions as their likely locations on chromosomes. Loss of heterozygosity is elicited at the molecular or cytogenetic level as a deletion, a gene conversion, single or double homologous and nonhomologous mitotic recombinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
3

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 89 publications
1
51
0
3
Order By: Relevance
“…Moreover, no LOH locus has been reported at 2q1 in ESCC. 9,14,15 A growing body of evidence has indicated that in addition to mutational inactivation or deletion of tumor suppressor genes, epigenetic gene silencing plays a significant role in carcinogenesis of various human cancers. [16][17][18][19] Epigenetic events, which are important in normal cellular functions, are also critical factors during initiation and progression of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, no LOH locus has been reported at 2q1 in ESCC. 9,14,15 A growing body of evidence has indicated that in addition to mutational inactivation or deletion of tumor suppressor genes, epigenetic gene silencing plays a significant role in carcinogenesis of various human cancers. [16][17][18][19] Epigenetic events, which are important in normal cellular functions, are also critical factors during initiation and progression of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Allelic imbalance of chromosome 1p36 is one of the most frequent genetic alterations observed in various human cancers (Ragnarsson et al, 1999;Thiagalingam et al, 2002). Linkage analyses using microsatellite markers revealed deletions of 1p36 in nearly 50% of primary human lung cancers (Nomoto et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] The altered mRNA levels in cancer genomes are often related to gene amplification of growth factor receptors, or the loss of functional tumor suppressor genes through homozygous deletion or loss of heterozygosity. 5,6 Detection of such gene copy number changes has been achieved by comparative genomic hybridization analysis. 7 However, because loss of heterozygosity may be accompanied by chromosome multiplicity or duplication of a dysfunctional allele, the most reliable approach to identify loss of heterozygosity is through detection of locus-specific genotype loss using a panel of single nucleotide polymorphism (SNP) markers and short tandem repeat (STR) or microsatellite markers.…”
mentioning
confidence: 99%